Mass Spectrometry Based Proteomic Profiling for Pancreatic Cancer - Pawa, Nikhil; Wright, James M; Arulampalam, Tan H A (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Mass spectrometer schematic (Wikimedia Commons, by Devon Fyson)